If you were a kid during the civil rights movement - Hooks, Gwendolyn; Kennedy, Kelly (Illustrator) (New York, NY : Children's Press, an imprint of Scholastic Inc., 2017)
Looks at the history of the civil rights movement, including the story of African American twins Connie and Mark who witness and participate in it.
Meet Connie! -- Meet Mark! -- Map -- Timeline -- Words to know.
Includes index.
3.4
K-3.
K-3
Keywords: African Americans -- Civil rights -- History -- 20th century -- Juvenile literature; Children -- Southern States -- History -- 18th century -- Juvenile literature; Civil rights movements -- United States -- History -- 20th century -- Juvenile literature; African Americans; Children -- History; Civil rights movements; African Americans -- Civil rights -- History; Children -- Southern States -- History; Civil rights -- United States -- History; United States -- Race relations -- Juvenile literature